2020
DOI: 10.1088/1755-1315/492/1/012049
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical quality of biscuits in various compositions of wheat flour, dangke flour and sago flour

Abstract: Biscuits are processed food products made from flour; however, the supply of the flour depends heavily on foreign producers. This study aimed to examine the use of dangke flour and sago flour to substitute wheat flour in biscuit formulations. The design used was a completely randomized design (CRD) of one factor. The treatments of the compositions of wheat flour, dangke flour, and sago flour (%) in the biscuit formulation were100: 0: 0; 80: 20: 0; 60:30:10; 40:40:20; 20:50:30; and 0:60:40 respectively. The res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…The water content that exceeded 5% in both treatments was caused by using peanuts without rst drying them. A low water content can cause the biscuit to taste burnt and be darker in colour, and if the water content value is high, the texture of the biscuit is not crunchy and can break (checking), and the taste changes more quickly during storage [21], [22]. Formula A3 was not tested for its nutritional content because the results of the organoleptic test showed that the percentage of people who liked formula A3 was lower compared to other formulas, or it could be said that formula A3 was least preferred in terms of its colour, aroma, and texture.…”
Section: Nutritional Content Test Results Of Modi Ed Biscuitsmentioning
confidence: 99%
“…The water content that exceeded 5% in both treatments was caused by using peanuts without rst drying them. A low water content can cause the biscuit to taste burnt and be darker in colour, and if the water content value is high, the texture of the biscuit is not crunchy and can break (checking), and the taste changes more quickly during storage [21], [22]. Formula A3 was not tested for its nutritional content because the results of the organoleptic test showed that the percentage of people who liked formula A3 was lower compared to other formulas, or it could be said that formula A3 was least preferred in terms of its colour, aroma, and texture.…”
Section: Nutritional Content Test Results Of Modi Ed Biscuitsmentioning
confidence: 99%